Body weight overestimation increases the risk of incident overweight among adolescents: Findings from a cohort study in Vietnam - Xuan Minh Tri Tran; Hoang Thuy Linh Nguyen; Thao Vi Tran; Sharifullah Alemi; Kaoruko Seino; Thang Van Vo; Keiko Nakamura (Clinical Epidemiology and Global Health, 2025)
Background: Overweight and obesity pose significant global health concerns, particularly among children and adolescents. This study aimed to examine the association between body weight misperception and the risk of incident overweight among Vietnamese adolescents over the three-year period. Methods: Data from the Hue Adolescents Cohort Study were used, including 353 secondary school students (mean age 11.60 ± 0.36 at baseline, 47.0 % girls), who completed questionnaires and anthropometric assessments. Based on the concordance between self-perceived and objectively measured body weight status, participants were categorized into three groups: underestimation, accurate perception, or overestimation. Logistic regression analysis, adjusted for socio-demographic characteristics and lifestyle behaviors, was conducted to assess the relationship between weight misperception and incident overweight. Results: Approximately half of the students exhibited body weight misperceptions, with males more likely to underestimate and females more likely to overestimate their weight. The cumulative and annual rates of incident overweight were 16.2 % and 5.0 %, respectively. Over the three-year follow-up, students who overestimated their body weight had significantly higher odds of developing overweight compared to those who accurate self-perception (adjusted odds ratio [aOR] = 2.855, 95 % confidence interval [CI] 1.163, 7.009). In contrast, students who underestimated their weight had lower odds of developing overweight (aOR = 0.323, 95 % CI 0.133, 0.786). Conclusions: This study highlights a notable incidence of overweight among Vietnamese adolescents and underscores the importance of addressing accurate body weight perceptions as part of strategies to prevent overweight.